A radical history of the world - Faulkner, Neil (Left book club, 2018)
Offers a historical study of the world that contends that history is continually created and recreated by conscious, collective human action. Faulkner argues that the struggles of the common people--slaves, serfs, handloom weavers, mine workers, women fighting oppression, black people fighting racism, colonized people fighting imperialism--these struggles, occasionally fusing into mass revolutionary upsurges, drive the historical process. He states that this is an approach to history that emphasizes agency, contingency, and the existence of alternatives; an approach that rejects the view that war and empire are inevitable, that there is no alternative to the market, and that greed, bullying, and violence are universal. In other words, Faulkner contends that the course of history is not predetermined, its outcome is not inevitable; it can go in different directions according to what human beings do.